Opportunities and challenges in Asian bee research and conservation - Warrit, Natapot (2023)
The challenges of bee research in Asia are unique and severe, and strategies andframeworks developed in North America or Europe may not prove applicable. Virtuallynone of these species have been assessed by the IUCN and there is a paucity ofpublic data on even the basics of bee distribution. If we do not know the speciespresent, their distribution and threats, we cannot protect them, but our knowledge baseis vanishing small in Asia compared to the rest of the world. To better understand andmeet these challenges, this Perspective conveys the ideas accumulated over hundredsof years of study in Asia, including academic, governmental, and other researchersfrom 13 Asian countries. We begin by outlining the special circumstances of Asian beeresearch and the current state of affairs, then highlighting the important of highly socialspecies as flagships for the lesser-known solitary bees, and then target areas in needof further study. From there, we outline a framework via which we will catalyze futureresearch in the region, especially via governmental and other partnerships necessaryto effectively conserve species.